Dynamic System Simulation to Improve the Effectiveness and Efficiency of Supply Chain Performance and Behaviour on Waste Bank Resik Becik - Ratih Setyaningrum; Vida Auralita; Dwi Izzhati; Pramudi Arsiwi; Tita Thalitha (International Journal of Technology)
Waste bank Resik Becik (BSRB) is one of the containers that help with waste management in the city of Semarang. Plastic waste that enters BSRB is collected, selected, and transformed into processed products with a sale value. Plastic waste that enters BSRB undergoes collection, selection, and transformation into processed products with saleable value. So, the flow of the supply chain process is one of the important elements of running the BSRB. Performance appraisal is the first step to improving the BSRB supply chain. The SCOR 11.0 (Supply Chain Operations Reference) method is a method of utilized for assessing supply chain performance. Various matrices are employed and customized to suit the company's specific conditions, enabling this method to represent the state of the company. The addition of this method is the AHP (Analytical Hierarchy Process) method as a determinant of the performance matrix weight and the normalization process. This allows the final value to be accurately determined. In this study, it was found that the supply chain conditions at BSRB were in good condition, with a value of 71.3438. The study of SCOR combined with dynamic systems can identify the five dimensions and interaction variables associated with the causal loop design model. SCOR models and dynamic systems provide more effective and efficient value by creating alternative scenarios. The first scenario is cutting indirect labour costs by $58,83. By adopting this alternative, BSRB reduces expenses from $580,25 to $639,07. Meanwhile, the second scenario involves scheduling waste collection from customers, which increases BSRB's expenditure to $681,35. The best scenario falls to the first scenario. The final result of this research is a simulation model in Powersim, or what is called a flow chart, that can show the entire supply chain system and its relevant systems.